A Case Study of Students with Learning Difficulties in Mathematics at Junior High School - Ratna, Ratna Maulida (Green Publisher Indonesia, 2025)
This study aims to identify and analyze the factors that cause learning difficulties in mathematics in Junior High School (SMP) students. The research method used is qualitative with a case study approach. Primary data were collected through observation, in-depth interviews with students, mathematics teachers, and parents, as well as documentation of student learning outcomes. The results of the study indicate that learning difficulties in mathematics are influenced by internal factors such as low motivation, anxiety towards mathematics, and weak understanding of concepts; and external factors such as less varied teaching methods and an unsupportive learning environment. These findings provide important insights for teachers and schools in designing more effective pedagogical interventions.